Determinants of the Public Budget Balance: The Role of Official Capital Flows - Andreas Steiner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Central banks invest their foreign exchange reserves predominantly in government securities. By means of a panel data analysis we examine the relationship between reserve currency status and public budget balance during different constellations of the international monetary system: the sterling period (1890-1935) and the dollar dominance (since World War II). We show for both periods that reserve currency status significantly lowers the public budget balance of the center countries.
Keywords: F31; F33; F41; H62; E62; C23; 330